Performance characteristics of the PowerFlow apheresis port: Early experience. Issue 6 (19th August 2019) - Garrity, Danielle; Graves, Molly; Linden, Jeanne; St. Pierre, Patricia; Ducharme, Paula; Zhao, Yong; Greene, Mindy; Vauthrin, Michelle; Weinstein, Robert
Abstract: We prospectively evaluated the Bard PowerFlow Implantable Apheresis IV Port in four patients undergoing outpatient therapeutic plasma exchange over 18 to 97 days. Three had bilateral internal jugular access ports, and one had a single left internal jugular access port for the inlet line with return via antecubital vein. Two patients receiving 5% albumin as replacement fluid achieved peak inlet flow of 99 ± 5 mL/min and 101 ± 6 mL/min, and peak plasma flow of 53 ± 6 and 47 ± 6 mL/min, respectively. Two patients receiving plasma as replacement fluid achieved peak inlet flow of 46 ± 7 and 85 ± 4 mL/min and peak plasma flow of 27 ± 3 and 35 ± 4 mL/min, respectively. Apheresis nurses accessed the ports on the first attempt in all procedures. Pressure alarms occurred in 6 of 47 procedures and were easily resolved by lowering the inlet rate by 10% in 5 of them. The PowerFlow shows promise as an implantable venous access device for apheresis.